Exploring the Landscape of Research in Islamic Education: A Bibliometric and Systematic Review - Zuhri Zuhri (AL-ISHLAH: Jurnal Pendidikan, 2023)
Effective management is a critical component in the success and development of any organization, and educational institutions are no exception. Effective management is particularly essential in the context of Islamic education, where it is crucial for achieving educational objectives and fostering students' moral and ethical values. In recent years, there has been a growing interest in studying management in Islamic education, resulting in numerous studies on the topic. However, despite the increasing attention to management in Islamic education, there is a lack of comprehensive and systematic reviews of the literature. Bibliometric analysis provides an objective and quantitative approach to address this gap by mapping the research trends, themes, and gaps in the literature. This study aims to conduct a systematic review of management in Islamic education using bibliometric analysis. Specifically, it seeks to answer the following research questions (RQ): a) What are the research trends and patterns in the literature on management in Islamic education, b) What are the primary themes and concepts related to management in Islamic education, c) What are the research gaps and opportunities for future studies. By answering these questions, this study aims to provide a thorough and current review of the literature on management in Islamic education. The results may be beneficial for researchers, policymakers, and practitioners in the field of Islamic education to better understand the current state of research and identify areas for further research and development.